2006
DOI: 10.1242/jeb.02298
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity-induced modifications of the vestibuloocular reflex inXenopus laevistadpoles are related to development and the occurrence of tail lordosis

Abstract: SUMMARY During space flights, tadpoles of the clawed toad Xenopus laevisoccasionally develop upward bended tails (tail lordosis). The tail lordosis disappears after re-entry to 1g within a couple of days. The mechanisms responsible for the induction of the tail lordosis are unknown;physical conditions such as weight de-loading or physiological factors such as decreased vestibular activity in microgravity might contribute. Microgravity(μg) also exerts significant effects on the roll-induced vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…The tadpoles, launched at the early tailbud stage (approximately one day old), exhibited caudal lordosis (also noted in a study by Horn, 2006), disproportionately long tails and short bodies, a failure to inflate their lungs, and a reduced, misshapen branchial apparatus (Snetkova et al, 1995). The acceleration and vibration of the launch and the sudden onset of μG may have caused or contributed to these irregularities.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The tadpoles, launched at the early tailbud stage (approximately one day old), exhibited caudal lordosis (also noted in a study by Horn, 2006), disproportionately long tails and short bodies, a failure to inflate their lungs, and a reduced, misshapen branchial apparatus (Snetkova et al, 1995). The acceleration and vibration of the launch and the sudden onset of μG may have caused or contributed to these irregularities.…”
Section: Introductionmentioning
confidence: 63%
“…Both swimming behavior and optomotor response were sometimes altered in the tadpoles raised in μG, but tadpoles would normalize upon return to normal gravity (Souza et al, 1995;Fejtek et al, 1998). Other studies involving exposure to spaceflight μG during development in Xenopus have found alterations in the development of the vestibular apparatus (Souza et al, 1994;Pronych et al, 1996) and vestibuloocular reflex (Sebastian and Horn, 2001;Horn, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Immediately before the rVOR recording, we documented tail morphology. Previous studies of the relationship between tail shape and vestibuloocular reflex after spaceflights revealed that the rVOR in tadpoles with abnormal tails differs from those with normal tails in an age-related manner (Horn, 2006;Horn and Gabriel, 2011).…”
Section: Recordings Of the Rvormentioning
confidence: 97%
“…This curve was used to calculate the rVOR amplitude, which is the maximal peak-to-peak movement of the eyes during a 360deg lateral roll. Previous studies in Xenopus laevis, young fish (Oreochromis mossambicus) and salamander larvae (Pleurodeles waltl) have shown that the rVOR amplitude is a sensitive indicator to describe (1) modifications of the rVOR during development (Horn et al, 1986a;Sebastian and Horn, 1999;Gabriel et al, 2012), (2) the susceptibility to changes within the vestibuloocular system induced by vestibular lesions (Horn et al, 1986b), (3) the extent of vestibular plasticity after such lesions (Rayer and Horn, 1986) and (4) the impact of altered gravitational conditions on vestibular function (Horn 2006;Sebastian et al, 2001;Horn and Gabriel, 2011;Gabriel et al, 2012). The rVOR amplitude was determined by the angular difference between the mean of eye angles recorded for roll angles between 60deg to 120deg and 240deg to 300deg, respectively (cf.…”
Section: Recordings Of the Rvormentioning
confidence: 99%
See 1 more Smart Citation